Analisis Teoritis Kasus Bullying: Telaah Kontrol Emosi Mario Dandy Dengan Pendekatan Teori Pengendalian Diri Hurlock - Himmah, Elok Rofiqotul; Susanti, Maulani; Rofiqi, Ahmad Nailur; Fitriana, Ani Qotuz Zuhro’ (CV. ITTC INDONESIA, 2023)
Adolescents as individuals are in the process of developing or becoming, namely developing towards maturity or independence. Teenagers need guidance because they still lack understanding or insight about themselves and environment and experience in determining the direction of his life to reach maturity. Therefore, adolescents are expected to be able to anticipate the consequences that lead to deviant behavior. In this study aims to determine the beginning of the conflict. This study uses a qualitative approach theory-driven case study. Researchers collected data by reading several journal articles and re-reading the literature. The results of this study aim to examine cases of bullying as well as Mario's emotional control and self-control. Bullying in Indonesian is known as